Influence of long-term fertilization on soil microbial biomass and dehydrogenase activity in relation to crop productivity in an acid Inceptisols - Purohit, Debasis; Mandal, Mitali; Dash, Avisek; Rout, Kumbha Karna; Panda, Narayan; Singh, Muneswar (ORYZA-An International Journal of Rice, 2019)
An effective approach for improving nutrient use efficiency and crop productivity simultaneously through exploitation of biological potential for efficient acquisition and utilization of nutrients by crops is very much needed in this current era. Thus, an attempt is made here to investigate the impact of long term fertilization in the soil ecology in rice-rice cropping system in post kharif - 2015 in flooded tropical rice (Oryza sativa L.) in an acidic sandy soil. The experiment was laid out in a randomized block design with quadruplicated treatments. Soil samples at different growth stages of rice were collected from long term fertilizer experiment.The studied long-term manured treatments included 100 % N, 100% NP, 100 % NPK, 150 % NPK and 100 % NPK+FYM (5t ha-1) and an unmanured control. Soil fertility status like SOC content and other available nutrient content has decreased continuously towards the crop growth period. Comparing the results of different treatments, it wasfound that the application of 100% NPK + FYM exhibited highest nutrient content in soils. With regards to microbial properties it was also observed that the amount of microbial biomass carbon (MBC) and microbialbiomass nitrogen ( MBN) showed highest accumulation in 100 % NPK + FYM at maximum tillering stage of the rice. The results further reveal that dehydrogenase activity was maximum at panicle initiation stage and thereafterit decreases. Soil organic carbon content, MBC, MBN and dehydrogenase activity were significantly correlated with each other. Significant correlations were observed between rice yield and MBC at maturity stage( R2 = 0.94**) and panicle initiation stage( R2 = 0.92**) and available nitrogen content at maturity stage( R2 = 0.91**).